The Cambridge companion to postmodern theology - Vanhoozer, Kevin J. (Cambridge companions to religion, 2003)
Postmodernity allows for no absolutes and no essence. Yet theology is concerned with the absolute, the essential. How then does theology sit within postmodernity? Is postmodern theology possible, or is such a concept a contradiction in terms? Should theology bother about postmodernism or just get on with its own thing? Can it? Theologians have responded in many different ways to the challenges posed by theories of postmodernity. In this introductory 2003 guide to a complex area, editor Kevin J. Vanhoozer addresses the issue head on in a lively survey of what 'talk about God' might mean in a postmodern age, and vice versa. The book then offers examples of different types of contemporary theology in relation to postmodernity, while the second part examines the key Christian doctrines in postmodern perspective. Leading theologians contribute to this clear and informative Companion, which no student of theology should be without.